Anaesthetic concerns of difficult airway in case of large oral hemangioma posted for robotic cystectomy - Kapadia, Khevna; Shah, Sheetal; Mehta, Hemant; Mehta, Misha (International Journal of Research in Medical Sciences, 2020)
A difficult airway poses a challenge to attending anaesthesiologist. Fibreoptic intubation (FOI) to secure airway can be a valuable option in such a scenario. Steep Trendelenberg’s position with pneumoperitoneum in robotic surgery causes respiratory changes with airway oedema and congestion. We are describing here a case report of 56-year male patient with a large congenital oral cavity hemangioma with primary urothelial neoplasm of bladder posted for robotic radical cystectomy with ileal conduit with urethrectomy. We emphasize the importance of difficult airway management by using fibre optic technique in such cases complicated by steep Trendelenburg’s position required during robotic surgeries.